Arbuscular mycorrhizal fungi and soil quality: a synthesis focused on West Africa - Djalole, Mèyendou; Gbogbo, Koffi Apeti; Domedjui, Komi Lucien; Folega, Fousseni; Batawila , Komlan; Akpagana, Koffi (Revue Ecosystèmes et Paysages, 2025)
Arbuscular mycorrhizal fungi (AMF) are root symbionts that play a crucial role in soil health and the resilience of agroecosystems, particularly in West Africa, where soils are often degraded. This literature review analyzes the evolution of research on AMF, their mechanisms of action on soil structure and fertility (glomalin, biogeochemical cycles), as well as their potential for carbon sequestration. A bibliometric approach was used to select and analyze 887 relevant publications from international databases. It reveals a significant increase in publications on AMF over the past three decades, reflecting a growing interest in these organisms. The taxonomic diversity of AMF is influenced by multiple environmental and anthropogenic factors, with notable variations according to ecological zones and land management systems. AMF improve soil quality through several mechanisms: aggregate structuring via glomalin production, contribution to biogeochemical cycles, enhancement of plant resistance to stress, etc. This synthesis also highlights the still underexplored richness of AMF diversity in West Africa, particularly in Togo, and emphasizes their usefulness in strengthening sustainable agriculture in the face of climate challenges. Research perspectives are proposed to address the identified gaps and promote the use of these microorganisms in local agricultural practices.